Psychological impact of testing for thrombophilic alterations - Legnani, Cristina; Razzaboni, Elisabetta; Gremigni, Paola; Bitti, Pio Enrico Ricci; Favaretto, Elisabetta; Palareti, Gualtiero (Thrombosis and Haemostasis, 2006)
We investigated the psychological impact of testing for the presence of thrombophilic alterations. The enrolled subjects received counseling from a physician before blood sampling and after receiving results, with a view to provide clear information about the aim of thrombophilia screening (TS). Participants were requested to completea pre-test questionnaire during this interview and a post-test questionnaire 20 days after receiving theTS results. One hundred ninety-seven subjects completed the pre-test questionnaire and 140/197 (71.1%) returned the post-test one. The TS results were altered in 36 (25.7%, R506Q mutation n=19; G20210A mutation n=9; antithrombin deficiency n=1; LAC phenomenon n=4; hyperhomocysteinemia n=3) and normal in 104 subjects. We assessed: perceived health status (PHS), state of anxiety, health fears, depressive reactions, moods, perceived well-being, and perceived daily-life stress. For both groups, both at pre- and post-test, none of the psychological variable scores showed significant worsening, regardless of whether TS resulted altered or normal. Anxiety significantly (p≤0.05) decreased at post-test in the altered group and a nonsignificant improvement in PHS after TS result communication was recorded in both groups. Age was an important factor in mediating psychological impact. In conclusion, diagnosis of thrombophilic alterations seems to be well accepted in the short term and TS should not be discouraged for potential adverse psychological effects. However, the psychological impact over a longer period of receiving altered results needs to be further investigated. The relationship between absence of adverse psychological reactions and quality of counseling program provided before and after TS should also be investigated.
Keywords: Psychological impact; thrombophilia; screening; risk factors